Fragmentation : new production patterns in the world economy - Arndt, Sven W.; Kierzkowski, Henryk (Oxford : Oxford University Press, 2001)
As the world economy becomes more integrated, and industry becomes more globalised, constituent parts of products are made all over the world. This volume explores the theoretical implications and empirical manifestations of this phenomenon.
Includes bibliographical references and index.
lje 23/08/16
Loans
Keywords: International division of labor; Offshore assembly industry; International business enterprises; Globalization